Russian energy strategy in the Asia-Pacific: Implications for Australia - Elizabeth Buchanan (ANU Press, 2021)
Given Australia's lack of energy security strategy, it is not surprising that the country is void of institutional knowledge and know-how of Russian foreign energy strategy. The 'lucky country' as it were, relies entirely on sea-lines of communication to the north to supply fuel and to export Australian coal and natural gas. Australia has entered the 2020s as the world's largest liquefied natural gas (LNG) exporter; however, maintaining complacency in Canberra's current export activities will ultimately lead to a long-term security crisis. This book critically examines Russian energy strategy in the Asia-Pacific, with a view to determining the security implications for Australia. Russia is important for global energy security chains because of its vast resource wealth and its geographical position - a pivotal position to supply both the European and Asian markets. Australia has no such luxury, geographically constrained as an island continent; it relies on the nearby Asia-Pacific import market to demand our energy and to facilitate the delivery of our national oil supplies. Understanding Russian foreign energy strategy in the region is crucial given the growing energy requirements in Australia's emerging Asia-Pacific arena.
Keywords: 330; Russia; energy; Russia Asia-Pacific; Putin; Energiepolitik; Energiemarkt; Energiewirtschaft; Internationale Wirtschaftsbeziehungen; Russland; Asiatisch-pazifischer Raum; Australien